Persistence of Unfairness and Inequality in Colombia’s Education (Papeles, 2018)
This paper shows how inequity and inequality in Colombian education are negatively correlated with several indices of poverty and of performance in tests like Saber 11 (High-School exit). Inequity and inequality are associated in a spatial way with the poorest regions that cast more Yes-votes in favor of Peace Plebiscite, regions where there has been little or no State presence during decades but now have some hope of being included in the regional development path in the current post-conflict policy. This paper argues how programs like Ser Pilo Paga favor private education and increase inequity. Education as a common good implies that the right not only to “receive some education”, but “to be well educated” or “to have a quality education” implies a combination of market and non-market goods and services that support the realization of this right to education.
Keywords: higher education; economic development; inequality; regional development